Florpyrauxifen-benzyl Weed Control Spectrum and Tank-Mix Compatibility with other Commonly Applied Herbicides in Rice. (19th February 2018) - Miller, M. Ryan; Norsworthy, Jason K.
Abstract: Florpyrauxifen-benzyl is a new herbicide being developed for rice. Research is needed to understand its spectrum of control and optimal tank-mix partners. Multiple greenhouse and field experiments were conducted to evaluate florpyrauxifen-benzyl efficacy and tank-mix compatibility. In greenhouse experiments, florpyrauxifen-benzyl at 30 g ai ha –1 provided ≥75% control of all weed species evaluated (broadleaf signalgrass, barnyardgrass, Amazon sprangletop, large crabgrass, northern jointvetch, hemp sesbania, pitted morningglory, Palmer amaranth, yellow nutsedge, rice flatsedge, smallflower umbrellasedge), and control was similar to or better than other herbicide options currently available in rice. Barnyardgrass was controlled 97% with florpyrauxifen-benzyl at 30 g ha –1, ultimately reducing height (86%) and aboveground biomass (84%). In these field studies at 30 g ha –1, no antagonism was observed when florpyrauxifen-benzyl was tank-mixed with contact (acifluorfen, bentazon, carfentrazone, propanil, and saflufenacil) or systemic (2, 4-D, bispyribac, cyhalofop, fenoxaprop, halosulfuron, imazethapyr, penoxsulam, quinclorac, and triclopyr) rice herbicides. Although not every tank-mix or weed species was evaluated, the lack of antagonistic interactions herein highlights the flexibility and versatility of this new herbicide. Once florpyrauxifen-benzyl becomes commercially available, it will be beneficial to tank-mix this new herbicide with others without sacrificing efficacy, so as to apply multiple sites of action together and thus lessen the risk for evolution of herbicide resistance.